Experimental Analysis of Melting Behavior of Capric Acid (CA)-Stearic Acid (SA) Eutectic Mixture and its 3D Numerical Solution of Natural Convection in a Cup - Cosanay, Hakan; Selimefendigil, Fatih; Öztop, Hakan Fehmi; Sari, Ahmet (Springer Heidelberg, 2022)
Computational studies were performed to investigate the melting process in a cubical closed space. Capric acid (CA)-stearic acid (SA) eutectic mixture is chosen as a phase change material (PCM). Some thermo-physical properties such as melting temperature, latent heat of fusion, specific heat capacity, thermal conductivity, thermal expansion coefficient, density and viscosity of CA-SA eutectic mixture prepared as PCM were measured. Considering these measured properties, the melting behavior of the prepared eutectic PCM was simulated numerically with finite volume method in a three-dimensional cavity. Non-isothermal heating conditions throughout phase change process of the PCM are considered in the numerical modeling study. It is shown that temperature difference has a significant impact on the melting, while its behavior changes for various cross sections. It is observed that the melting does not change after 80 min for the studied PCM. Significant variations for the melting behavior are observed between 2D and 3D configurations. Melt fraction is only 1.20% higher in 3D case as compared to 2D case at t = 130 min and Gr = 1.8 x 10(5), while this value is 1.08% at Gr = 3.6 x 10(4).
Keywords: Phase change material; Energy Storage; Numerical simulation; Finite volume method